Eco-Design Case-Based Reasoning Tool: The Integration of Ecological Quality Function Deployment and Case-Based Reasoning Methods for Supporting Sustainable Product Design - Awanis, Romli; Setchi, Rossitza; Prickett, Paul; De la Pisa, Miguel (SAGE Journals, 2016)
Several methods and tools have been developed to facilitate sustainable product design, but they lack critical application of the ecological design (eco-design) process and economic costing, particularly during the conceptual design phase. This research study overcomes these deficiencies by integrating eco-design approaches across all phases of the product life cycle. It proposes an eco-design case-based reasoning tool that is integrated with the recently developed ecological quality function deployment method, which supports sustainable product design. The eco-design case-based reasoning tool is an intuitive decision-support tool that complements the ecological quality function deployment method and proposes solutions related to customers’ requirements and the environmental and economic impacts of the product. The ecological quality function deployment method ensures that customers’ needs are considered within the context of product sustainability. The novelty of this article is in the development of the eco-design case-based reasoning tool which is based on the premise that if experiences from the ecological quality function deployment process can be captured in some useful form, designers can refer to and learn from them. This approach helps industrial decision-makers propose solutions by reusing solutions from similar cases and from their past experiences. The novelty is in the way the cases are structured and new cases are generated, using life-cycle assessments, cost estimations, and information about related manufacturing processes and means of transportation. This article demonstrates the applicability of the proposed approach through an industrial case study.